Global trend in waqf research: a general bibliometric and conceptual structure approach using biblioshiny - Ruslan, Ashraff; Abdul Rasool, Saladin (2023)
The purpose of this study was to explore the current status, trends, and conceptual structure of research on Waqf by doing a bibliometric analysis. Bibliometric analysis was performed with a package called Biblioshiny from R-Studio. The current study applies bibliometric quantitative methods and conceptual structure in knowledge discoveries. In the foreground, on August 18, 2023, the screening process utilized looked for all references to "Waqf" OR “Waqaf" in Scopus' "article title" and discovered 658 scholarly contributions from 1914 to 2023. A total of 658 documents authored by 1,188 scholars in 247 journals published in the Scopus database between 1914 and 2023 were included in the present bibliometric analysis. A total of 31 countries worked together in contributing to the waqf research in the database. There were 332 affiliations between the universities or institutes where the authors served. Current literature on Waqf in the Ottoman and real estate context is matured, which stresses the need for more research productivity, especially within areas regarding Waqf related to management, assets, cash waqf, waqf institutions as well as waqf formulation that now becoming the new direction and focus of future research. One of the study's limitations is that the data for this study was only gathered from the Scopus database. It would be far more advantageous if other researchers could conduct bibliometric analyses of Waqf by combining the data from Dimensions, PubMed, Web of Science (WoS/Wok), the Cochrane Library, or another database. Furthermore, this study could be improved if the bibliometric analysis included Author and Source Impact, Lotka's Law, Bradford's Law, and other bibliometric elements for descriptive analysis. Intellectual and Social structure could be explored in future research. It will help the researcher to perform bibliometric analysis in any field with a clear research flow, from major online databases with an easy user interface in a very short time. This study allows the researcher to find the most significant author or article in the field of study in which they are interested by using the overview of earlier research provided by bibliometric analysis. It provides a thorough introduction to the research domain for scholars and practitioners who are interested in it. The cluster of research in the Waqf resulting from this study will help them focus on the next research area via a Co-occurrence Network and translated into thematic which will enhance the selection and focus of new research directions that have greater potential to contribute growth of the Waqf study significantly.